Quality of Life in the Context of Social Withdrawal in Japan - Olejarz, Sylwia (Current Problems of Psychiatry, 2011)
This article aims to investigate the issue of quality of life in the context of an attention-grabbing phenomenon – social withdrawal of youth in Japan. The s concept of quality of life is scrutinized at three levels: 1) the level of individual, 2) the level of family and 3) the level of community. In conclusion, the concept of “quality of life” is not only the indicator of personal or communal well-being (or its decline), but might also be used as “litmus paper” showing emerging transformation of values in the given culture.